Levures et champignons semblables aux levures dans la zone littorale roumaine de la Mer Noire - Apas, Mukadder Mujdaba (Cercetări Marine - Recherches Marines, 2026)
Results on spreading of viable cells of yeasts and yeast-like fungi along the Romanian Sea shore, throughout 1975-1977, are here presented. Analyzed samples originated from 14 points situated just in the zone undergone to the waste waters discharge, as well as, from a point 5 Miles far from the shores. Ten species of yeast and yeast-like fungi were isolated. Total number of cells /liters was always much bigger in shallow than in neritic area.